A case study examining the Turkish language skills of bilingual children according to adverse teaching conditions - Sonmez, Hulya (Walter De Gruyter Gmbh, 2023)
In the research, the effect of adverse teaching conditions on the Turkish listening comprehension, speaking, written expression, and reading comprehension skills of bilingual students was investigated. In the study, some indicators of the basic language skills of bilingual children were examined according to the multi-grade classroom and COVID-19 factors. The universe of the study is bilingual children studying in multi-grade classrooms of primary education in Mus province. The population is made up of sixty-nine third and fourth-year students from four different primary schools. Three questions were analyzed: (1) What is the level of students' listening comprehension, speaking, written expression, and reading com-prehension skills? (2) How is the effect of independent variables (gender, age of acquisition of Turkish, school level, parents' education, and school) on students' language skills? (3) How is the relationship between students' listening comprehen-sion, speaking, written expression, and reading comprehension skills? The study adopted a multiple-case study design. The data were collected using two rubrics and two achievement tests. Data were analyzed using descriptive statistics, multiple group comparisons, nonparametric tests, and correlation. The results revealed find-ings regarding participants' listening comprehension, speaking, written expression, and reading comprehension skills. It was observed that the independent variables did not significantly affect the language skills of the participants. According to the findings, students' language indicators of written expression are weak and rela-tively inadequate. Alike students' language indicators of reading comprehension are partially inadequate. On the other hand, the indicators in speaking and listening comprehension skills were observed to be good but partially insufficient. The re-sults show that the performance of bilingual students in multi-grade classrooms on Turkish language indicators observed during the COVID-19 outbreak is not at an adequate level completely.
Keywords: Multi-Grade Classroom; Adverse Conditions; Bilingual Children; Pandemic; Multilingual Education; Immigrant Parents; English-Language; Teachers Views; Multigrade; Speaking; Instruction; Achievement; Exploration; Outcomes